Comparative Risk of Venous Thromboembolism in Rheumatoid Arthritis Patients Receiving Tofacitinib Versus Those Receiving Tumor Necrosis Factor Inhibitors: An Observational Cohort Study. Issue 6 (29th April 2019) - Desai, Rishi J.; Pawar, Ajinkya; Weinblatt, Michael E.; Kim, Seoyoung C.
Abstract : Objective: To evaluate the risk of venous thromboembolism (VTE) in rheumatoid arthritis (RA) patients receiving tofacitinib versus those receiving tumor necrosis factor (TNF) inhibitors. Methods: RA patients who were initiating treatment with tofacitinib or a TNF inhibitor and had not previously received any biologic agent or tofacitinib were identified from the Truven MarketScan database (2012–2016) or Medicare claims (parts A, B, and D) database (2012–2015). Patients were followed up until treatment discontinuation, treatment switch, insurance disenrollment, or administrative censoring. The outcome of VTE was identified using inpatient claims for pulmonary embolism or deep vein thrombosis. Hazard ratios (HRs) and 95% confidence intervals (95% CIs) were determined using a Cox proportional hazards model after accounting for confounding through propensity score–based fine‐stratification weighting. HRs were pooled across databases using the inverse variance meta‐analytic method. Results: A total of 34, 074 RA patients (mean age 50 years; 5.6% tofacitinib initiators) and 17, 086 RA patients (mean age 71 years; 5.8% tofacitinib initiators) were identified from the Truven and Medicare databases, respectively. The crude incidence rates of VTE per 100 person‐years were 0.60 (95% CI 0.26–1.19) and 0.34 (95% CI 0.27–0.41) in Truven and 1.12 (95% CI 0.45–2.31) and 0.92 (95% CI 0.76–1.11) in Medicare for patients receiving tofacitinib and patients receiving TNF inhibitors, respectively. Propensity score–adjusted HRs showed no significant differences in the risk of VTE between tofacitinib‐treated and TNF inhibitor–treated patients in either database, with a pooled HR of 1.33 (95% CI 0.78–2.24). Conclusion: Occurrence of VTE in a total of 50, 865 RA patients initiating treatment with tofacitinib or a TNF inhibitor was infrequent (<1 per 100 person‐years). We observed a numerically higher, but statistically nonsignificant, risk of VTE in RA patients receiving tofacitinib versus those receiving TNF inhibitors.